Determinasi Sistem Informasi Pemberitahuan Impor Barang: Internet, Komputer dan Brainware (Literature Review) - iin - indrawati; Hapzi Ali - Universitas Bhayangkara Jakarta Raya (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2022)
Abstract - Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research works to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that affect the Import Notification Information System, namely: Internet, Computers and Brainware, a study of Human Resource Management literature. The results of this literature review article are: 1) Internet has an effect on the Information System for Notification of Import of Goods; 2) Computers affect the Goods Import Notification Information System; and 3) Brainware affects the Goods Import Notification Information System.Keywords: Information System for Notification of Import of Goods, Internet, Computer and Brainware Abstrak - Riset terdahulu atau riset yang relevan sangat penting dalam suatu riset atau artikel ilmiah. Riset terdahulu atau riset yang relevan berfungsi untuk memperkuat teori dan penomena hubungan atau pengaruh antar variable. Artikel ini mereview Faktor-faktor yang mempengaruhi Sistem Informasi Pemberitahuan Impor Barang, yaitu: Internet, Komputer dan Brainware, suatu studi literatur Manajemen Sumberdaya Manusia. Hasil artikel literature review ini adalah: 1) Internet berpengaruh terhadap Sistem Informasi Pemberitahuan Impor Barang; 2) Komputer berpengaruh terhadap Sistem Informasi Pemberitahuan Impor Barang; dan 3) Brainware berpengaruh terhadap Sistem Informasi Pemberitahuan Impor Barang.Kata Kunci : Sistem Informasi Pemberitahuan Impor Barang, Internet, Komputer dan Brainware